2000
DOI: 10.1128/aem.66.4.1292-1297.2000
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Generation in Microbial Fuel Cells Using Neutral Red as an Electronophore

Abstract: Neutral red (NR) was utilized as an electron mediator in microbial fuel cells consuming glucose to study both its efficiency during electricity generation and its role in altering anaerobic growth and metabolism of Escherichia coli and Actinobacillus succinogenes. A study of chemical fuel cells in which NADH, NR, and ferricyanide were the electron donor, the electronophore, and the electron acceptor, respectively, showed that electrical current produced from NADH was proportional to the concentration of NADH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
282
1
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(297 citation statements)
references
References 22 publications
8
282
1
6
Order By: Relevance
“…This ratio is 10-100 times larger than many traditional MFCs (1,2,17,19), but 200 times smaller than the ratio for our mini-MFC. Domestic wastewater was used in the anode, and the MFC operated with an air cathode (carbon cloth spiked with a Pt catalyst).…”
Section: Resultsmentioning
confidence: 52%
“…This ratio is 10-100 times larger than many traditional MFCs (1,2,17,19), but 200 times smaller than the ratio for our mini-MFC. Domestic wastewater was used in the anode, and the MFC operated with an air cathode (carbon cloth spiked with a Pt catalyst).…”
Section: Resultsmentioning
confidence: 52%
“…In addition to organic heterocyclic and monocyclic compounds, sulfur species and hydrogen can be used as electron shuttles (Lovley, 2000;Straub and Schink, 2004;Niessen et al, 2005;Rabaey et al, 2006). To mimic the microbial shuttling, redox-active compounds such as neutral red can be added to the anode compartment of an MFC (Park and Zeikus, 2000). In one study, it was shown that Escherichia coli species transported neutral red into the periplasmic space, where a hydrogenase-mediated reduction occurred (McKinlay and Zeikus, 2004).…”
Section: Electron Transfer Through Mobile Componentsmentioning
confidence: 99%
“…A system developed for harvesting electricity from marine or river sediments [16,17,28] makes it possible to produce useful electric energy without aeration. However, this system depends on a redox potential difference between the anaerobic sediment and the upper aerobic layer of seawater, making the proton gradient difficult to conserve and resulting in an efficiency that may be lower than in a reactor-type MFC [24,27].…”
Section: Discussionmentioning
confidence: 99%